Milo Calkin papers - Calkin, Milo, 1810-1872.; Eckhart, George Boland, 1897-
Photocopy and transcript of journal kept by Calkin as a carpenter aboard the whaling ship, Independence, on its voyage from Nantucket, Mass., to the South Pacific Ocean. Calkin made the trip on the advice of his physician as a cure for asthma. Includes description and sketches of whaling, shipwreck on Starbuck Island (Kirihati), subsequent boat trip to Rarotonga (Cook Islands) and Hawaii, Calkin's years in Hawaii as a clerk in a mercantile firm, and his return to the U.S. (1842). Also includes an introduction to the journal written in 1953 by George Boland Eckhart, biographical information concerning Calkin, and a map (1952).
Microfilm produced from originals in the Huntington Library.
California: Henry E. Huntington Library, San Marino
Businessman, librarian, and shipwright.
Collection material in English.
Keywords: Independence (Whaling ship); Asthma; Shipwrecks -- Kiribati -- Starbuck Islands; Voyages and travels; Whaling -- Massachusetts; Whaling -- South Pacific Ocean; Hawaii -- Commerce; Hawaii -- Description and travel; Nantucket (Mass.) -- Description and travel; Rarotonga (Cook Islands) -- Description and travel; Businessmen; Librarians; Shipwrights